Computer-Aided Design to Improve the Thermal Stability of Rhizomucor miehei Lipase - Rong Teng; Jin Zhang; Zhui Tu; Qinghua He; Yanping Li (Foods, 2024)
Lipase, a green biocatalyst, finds extensive application in the food sector. Enhancing the thermal stability of lipase presents both challenges and opportunities within the food industry. This research employed multiple rounds of cross-screening using tools like FoldX and I-Mutant 3.0 to strategically design mutations for Rhizomucor miehei lipase (RML), resulting in eight unique single-point mutation designs. E230I, N120M, and N264M have been confirmed experimentally to be potential combination mutation candidates. The resulting triple mutant N120M/E230I/N264M showed a higher thermal stability, with an optimum temperature of 55 °C, 10 °C higher than that of the wild-type RML. The half-life was extended from 46 to 462 min at 50 °C. Furthermore, the catalytic activity of N120M/E230I/N264M on camphor tree seed oil increased by 140% to 600 U/mg, which aids in the production of novel structured lipids. Using molecular docking and molecular dynamics simulations, we analyzed the molecular mechanism of enhanced thermal stability. This study validated the efficacy and dependability of computer-aided design to generate heat-resistant RML mutants and indicated that RML N120M/E230I/N264M lipase can be used as an effective biocatalyst for fat processing in the food industry.